Prediktor mortalitas pada pasien dengan stenosis aorta berat yang menjalani percutaneus aortic balloon valvuloplasty - D Fernando; F Amelia; NRV Barus; A Kurniawan; R Tanoto; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2010)
Background: Percutaneus aortic balloon valvuloplasty as one of the therapies available for aortic stenosis is associated with a high mortality rate after the intervention.Aim: To determine the predictors of mortality in patients who had under-gone percutaneus balloon aortic valvuloplasty.Methods: A search was conducted on Pubmed and Proquest. After screen-ing titles and abstracts by inclusion and exclusion criteria, five articles were available as full texts. Three articles were considered useful by the authors.Results: Each of the three articles showed mostly different predictors of outcome, while all of them showed the mortality rate was high in patients after undergoing percutaneus balloon aortic valvuloplasty. The predictors in the first article are baseline functional status renal function, female gen-der, mitral regurgitation severity, baseline cardiac output, cachexia, and left ventricular systolic function. The second article showed only advancing age as a strong predictor. In the third article the predictors are left ventricular ejection fraction, pulmonary artery systolic pressure, pulmonary vascular resistance, and right ventricular end-diastolic pressure.Conclusion: Mortality rate in patients who had undergone percutaneus balloon aortic valvuloplasty is high, with baseline functional status renal function, female gender, mitral regurgitation severity, baseline cardiac output, cachexia, left ventricular systolic function, and advancing age as predictors of mortality.